ANALISIS YURIDIS TERHADAP KEWAJIBAN PEMBAYARAN IMBALAN BAGI KURATOR (STUDI KASUS PUTUSAN PENETAPAN NOMOR 48/PAILIT/2012/PN.NIAGA. JKT.PST JO NOMOR 704 K/ PDT.SUS/2012 - Bachtiar, Maryati; Fitriani, Riska; ', Jumdesra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia's economy was shocked by the news of PT. Cellular telecommunications (PT Telkomsel) were declared bankrupt by the Commercial Court on 14 September 2012. Telkomsel cut off bankruptcy by the Central Jakarta Commercial Court Decision Case Number 48/Pailit/2012/PN.Niaga.Jkt.Pst. because judged not meet obligations to partners, PT. Prima Jaya Informatika. However, the Bankruptcy Decision subsequently canceled by the Supreme Court. However, natural bankruptcy at the end of the PT. Telkomsel is not the end result of the law that must be paid by Telkomsel namely Rewards For curator.In conducting the study, the authors formulate two formulation of the problem, namely: The first How to Position the Receiver in bankruptcy cases Telkomsel in Decision Determination of Number 48/Pailit/2012/PN.Niaga.Jkt.Pst Jo No. 704 K/Pdt.Sus/2012? Second, How to judge the legal considerations of the remuneration for the Curator dalamPutusan-related judgments Telkomsel Bankruptcy Decisions Determination Number 48/Pailit/2012/ PN.Niaga.Jkt.Pst Jo Number 704 K/Pdt.Sus/2012?.and three, How analyzes Determination Decision No. 48/Pailit/2012/ PN.Niaga.Jkt.Pst Jo Number 704 K/Pdt.Sus/2012?The results showed that: The First, Fees for the Receiver in bankruptcy case ends because the appeal or reconsideration decision, the amount of remuneration is determined by the judge and curator charged to the applicant or the applicant's bankruptcy and debtors in the ratio set by the panel of Judges. Second, Decision of the Commercial Court Decision on Central Jakarta District Court No. 48/Pailit/ 2012/PN.Niaga.Jkt.Pst Jo No. 704K/Pdt.Sus/2012 is not compatible with the principles of justice. And three, the judges who decide the benefits do not consider the work that has been done, ability, and employment rates Curator concerned in determining the amount of remuneration. And does not consider any new rules that have been born with regard to the provisions of the Guidelines amount of remuneration for the curators and Administrator (Rule of law and human rights minister Number 1 of 2013).Keywords: Bankruptcy Telkomsel – Curator – Curator Rewards